Human brain posseses the ability to create a concept to assist the process of grouping individual object or events into different classes or categories. We call this grouping process as categorization. In addition to humans, the ability to categorize has also been proposed for animals. Being able to identify, visually or otherwise, a new object as a member of a category is an advantage for animals. Present experiment aims to test the categorization ability in discriminating species by Macaca fas - KANTHI ARUM WIDAYATI; BAMBANG SURYOBROTO; ACHMAD FARAJALLAH; AKICHIKA MIKAMI (HAYATI Journal of Biosciences, 2011)
Human brain posseses the ability to create a concept to assist the process of grouping individual object or events into different classes or categories. We call this grouping process as categorization. In addition to humans, the ability to categorize has also been proposed for animals. Being able to identify, visually or otherwise, a new object as a member of a category is an advantage for animals. Present experiment aims to test the categorization ability in discriminating species by Macaca fascicularis. Using match-to-sample task with photographs of monkeys and human as stimuli, we tested whether monkeys able to categorize monkey individuals as a class against human individuals as another class. We found that monkeys categorized humans differently from monkeys. The monkeys used physical characteristic such as shape and colors from the photographs to create different concepts of human and monkeys.